THE EFFECT OF SERVICE QUALITY, BRAND IMAGE AND SALES PROMOTION ON CONSUMERS’ SATISFACTION AT PT. ASTRA HONDA MOTOR OF BENGKULU CITY - Yetri Oktiva Sari; Sri Handayani; Kamelia Astuty (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
Astra Honda Motor is a company engaged in manufacturing, assembling and distributing Honda brand and type motorbikes. Astra Honda Motor is the largest motorbike manufacturer in Indonesia. However, this year Astra Honda Motor's sales have decreased so it is necessary to find out what is the cause of the decline in sales. This research aims to determine the influence of service quality, brand image and sales promotion on customer satisfaction at PT. Astra Honda Motor Panorama. This type of research is correlational, namely research to determine the influence and level of influence between two or more variables without any attempt to influence these variables. The sample in this study used an accidental sampling technique, namely a method of determining the sample by taking respondents who happened to be present or available in a place according to the research context. Based on the results of the research that has been carried out, the results obtained are that the regression equation in this study is Y = 14.290 + 0.517 X1 + 0.569 X2 + 0.299 X3+ e. There is an influence of service quality (X1) on customer satisfaction (Y) of PT. Astra Honda Panorama Bengkulu Branch with a sig value of <0.05 and tcount> ttable (4.185>1.669) thus Ho is rejected and Ha is accepted. There is an influence of brand image (X2) on consumer satisfaction (Y) of PT. Astra Honda Panorama Bengkulu Branch with a sig value of 0.005 < 0.05 and tcount> ttable (5.786>1.669) thus Ho is rejected and Ha is accepted. There is an influence of promotion (X3) on consumer satisfaction (Y) of PT. Astra Honda Panorama Bengkulu Branch with a sig value of 0.000<0.05 and tcount>ttable (3.701>1.669) thus Ho is rejected and Ha is accepted. Service quality, brand image and sales promotion together influence consumer satisfaction with a value of Fcount 9.867 > Ftable 3.14, so it can be concluded that together the independent variables influence the dependent variable.